The language of suffering: Media discourse and public attitudes towards the MH17 air tragedy in Malaysia and the UK. Issue 5 (October 2019) - Theng Ong, Theng; McKenzie, Robert M.
'If it bleeds, it leads', events characterised by fatalities, are likely to attract high levels of media coverage. This study adopts a multidisciplinary approach to investigate public discourses on the MH17 tragedy in Malaysia and the United Kingdom. First, corpus-based discourse analysis was employed to explore the construction of the Malaysian Airlines tragedy MH17 in four selected Malaysian and British newspapers. In addition, an attitudinal study examining 50 Malaysian and 50 UK nationals' perceptions of the tragedy was conducted. Keywords analysis revealed an overall tendency for the news media to construct the air tragedy through classifications between 'us' and 'others'. Specifically, important 'Us' (Malaysian elites) and non-important 'Other' (non-Malaysian) in the Malaysian newspapers, versus good 'Us' (the West) and evil 'Others' (Russia) in the British newspapers. The attitudinal analysis shows, for both the Malaysian and the UK respondents, the most salient associations with the MH17 tragedy related to ' conflicts '.